The Effects of Compensation and Work Motivation Towards Turnover Intention - Taruna Anggapradja, Indra; Roespinoedji, Djoko (International Journal of Psychosocial Rehabilitation, 2020)
An employee is an asset to a company. Without contributions from employees, the company's goals will not be achieved. Compensation is a form of compensation from the company for the work done. Conducting employees' work requires the motivation to be well performing. This research aims to determine the effect of compensation on turnover intention. The method of research used is a descriptive and variation method. The results show that compensation affects the turnover of intention. Although there are still some elements that need to be considered because it has a low value that belongs to the category quite well. Work motivation affects the turnover of intention. Although there are still some elements that need to be considered because it has a low value that needs to be improved again, that is in the category quite good. Compensation and work affect the turnover intention based on the hypothesis test result. An employee is an asset to a company. Without contributions from employees, the company's goals will not be achieved. Compensation is a form of compensation from the company for the work done. Conducting employees' work requires the motivation to be well performing. This research aims to determine the effect of compensation on turnover intention. The method of research used is a descriptive and variation method. The results show that compensation affects the turnover of intention. Although there are still some elements that need to be considered because it has a low value that belongs to the category quite well. Work motivation affects the turnover of intention. Although there are still some elements that need to be considered because it has a low value that needs to be improved again, that is in the category quite good.